Cartilage markers in synovial fluid in symptomatic knee osteoarthritis - Petersson, Ingemar F; Sandqvist, Lars; Svensson, Björn; Saxne, Tore (Annals of the rheumatic diseases, 1997)
OBJECTIVE To investigate if the relative content of aggrecan and cartilage oligomeric matrix protein (COMP) in synovial fluid lavage samples differs between individuals with knee pain with or without evidence of radiological knee osteoarthritis (joint space narrowing). METHODS In a community based cohort of 204 individuals aged 35-54 years with chronic (>3 months duration) knee pain, a subgroup of 45 subjects with radiographic osteoarthritis, grade I according to the Ahlbäck classification, was randomly chosen; 45 individuals, age and sex matched from the same cohort with chronic knee pain but with normal radiographs, served as controls. Knee joint fluid was obtained by a standardised lavage procedure. The concentrations of aggrecan core protein epitopes and a cartilage matrix protein (COMP) were determined by immuno-assays and the aggrecan/COMP con-centration ratio was calculated. RESULTS The aggrecan/COMP ratio was higher (P < 0.001) in the group with radiographic osteoarthritis than in the control group. CONCLUSIONS The higher aggrecan/COMP ratios in osteoarthritis could reflect increased cartilage matrix turnover in osteoarthritis with predominant release of aggrecan fragments. Synovial fluid analysis of cartilage markers holds promise as a useful means of monitoring changes in the cartilage turnover in studies of pathogenic mechanisms in osteoarthritis.